New criteria for selecting the origin of DNA replication in Wolbachia and closely related bacteria - Baldo Laura; Bordenstein Seth R; Tsiamis Georgios; Siozios Stefanos; Sapountzis Panagiotis; Hotopp Julie; Ioannidis Panagiotis; Werren John H; Bourtzis Kostas (BMC Genomics, 2007)
Abstract Background The annotated genomes of two closely related strains of the intracellular bacterium Wolbachia pipientis have been reported without the identifications of the putative origin of replication (ori). Identifying the ori of these bacteria and related alpha-Proteobacteria as well as their patterns of sequence evolution will aid studies of cell replication and cell density, as well as the potential genetic manipulation of these widespread intracellular bacteria. Results Using features that have been previously experimentally verified in the alpha-Proteobacterium Caulobacter crescentus, the origin of DNA replication (ori) regions were identified in silico for Wolbachia strains and eleven other related bacteria belonging to Ehrlichia, Anaplasma, and Rickettsia genera. These features include DnaA-, CtrA- and IHF-binding sites as well as the flanking genes in C. crescentus. The Wolbachia ori boundary genes were found to be hemE and COG1253 protein (CBS domain protein). Comparisons of the putative ori region among related Wolbachia strains showed higher conservation of bases within binding sites. Conclusion The sequences of the ori regions described here are only similar among closely related bacteria while fundamental characteristics like presence of DnaA and IHF binding sites as well as the boundary genes are more widely conserved. The relative paucity of CtrA binding sites in the ori regions, as well as the absence of key enzymes associated with DNA replication in the respective genomes, suggest that several of these obligate intracellular bacteria may have altered replication mechanisms. Based on these analyses, criteria are set forth for identifying the ori region in genome sequencing projects.